The Urgency of Establishing Student Government Legislation as the Legal Foundation for Reforming Student Governance at Universitas Dian Nuswantoro - Suryawijaya, Tito; Fadhilah, Ahmad; Salsabila, Citra; Medantoro, Gabriella; Suksmaningtyas, Rania (Journal of Administration Studies, 2024)
This study aims to analyze the impact of designing the Legal Standing Student Government and changes in the governance structure of student administration at Universitas Dian Nuswantoro. A qualitative method was employed to delve into the policy implementation and organizational structural changes. The research subject will involve various related parties, including student organization administrators, members, and parties involved in the decision-making process in designing legal standing for student government. Data will be verified through triangulation, by comparing information from various sources, such as interviews, document analysis, and observations. Testing the legal standing design uses a normative analysis methodology. The research findings indicate a significant positive contribution, including improved organizational effectiveness and increased student participation. The originality of the study lies in the specific focus on the implementation of the design within the context of a particular university. The novelty of this research is manifested in the in-depth understanding of the impact of Legal Standing on the governance of student administration, providing a fresh perspective on the role and relevance of this policy in enhancing the quality of student organizations in higher education.